Development of smart bin apps for Kampar residence - Beh, Shin Yi (2024)
As the number of people using smart devices grows exponentially, mobile applications have become popular as effective solutions to various problems. Although there are many smart waste management software with scheduling systems, notification systems, route optimization systems, and reporting systems, the market still demands a comprehensive mobile application. Therefore, I want to offer “ProWaste”, a mobile application designed to provide an efficient way to manage waste in Kampar. Collectors and managers can use this app to manage waste in different residential areas of Kampar. Moreover, the smart waste bin app allows collectors to set reminders, reminding them to collect waste at specific locations on a given day, and collectors can report waste issues in their area to the manager using this app. Most importantly, Firebase is used to securely store user credentials. I plan to use the Mobile Application Development Lifecycle (MADLC) as the framework for developing this mobile app. Essentially, the app aims to help collectors effectively plan their weekly waste collection, optimize collection routes based on specified locations, and report issues to the manager efficiently.